PERCEIVED ENJOYMENT IN ONLINE SHOPPING VIA SOCIAL MEDIA AMONG GENERATION-Y - Fatin Farhana Kamis; Shah Iskandar Fahmie Ramlee (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
Social media has evolved as technology has shifted. Moreover, it has made it easier for users when it is updated to the application and can be used on smartphones. Enjoyment is the key to social media surfing and relieving stressful daily affairs. This paper examines the perceived happiness, and online purchase behaviours of Generation Y. Generation Y is the largest segment in the Malaysian population and also known as the largest internet user. This study aims to investigate the factor of online purchases among generation y through social media. This study also more focuses on three categories of social media from Facebook, Instagram, and Twitter. The quantitative method is used in this research to analyze the data. The data collected using an online survey via social media.